Overexpression of Global Regulator SCrp Leads to the Discovery of New Angucyclines in Streptomyces sp. XS-16 - Xiao Xu; Falei Zhang; Luning Zhou; Yimin Chang; Qian Che; Tianjiao Zhu; Dehai Li; Guojian Zhang (Marine Drugs, 2023)
Six angucyclines including three unreported compounds (1–3) were isolated from Streptomyces sp. XS-16 by overexpressing the native global regulator of SCrp (cyclic AMP receptor). The structures were characterized based on nuclear magnetic resonance (NMR) and spectrometry analysis and assisted by electronic circular dichroism (ECD) calculations. All compounds were tested for their antitumor and antimicrobial activities, and compound 1 showed different inhibitory activities against various tumor cell lines with IC50 values ranging from 0.32 to 5.33 μM.